Respostas

2013-10-23T10:26:00-02:00
1º )  5( x +1) + 3 ( y - 2) = 4
        5x +  5 + 3y - 6 = 4
         5x + 3y   = 4 - 5  - 6   
          5x + 3y = 4 - 10             1º termo arrumado
          5x + 3y = - 6
         
2º) 5x + 5 + 3y - 6 = 4
     5x + 3y =  4 - 5 + 6
       5x + 3y = 10 - 5
         5x + 3y  = 5      2º termo arrumado

{ 5x + 3y = -  6   x( -1)
{  5x +3y  = 5     

fica assim;
{ - 5 x - 3y   = 6
{   5x + 3y = 5          .

    não existe raizes par x e y = nulo
      
2 3 2